Thermal liquid biopsy for monitoring melanoma patients under surveillance during treatment: A pilot study - Velazquez-Campoy, Adrian; Vega, Sonia; Sanchez-Gracia, Oscar; Lanas, Angel; Rodrigo, Alberto; Kaliappan, Alagammai; Hall, Melissa Barousse; Nguyen, Taylor Q.; Brock, Guy N.; Chesney, Jason A.; Garbett, Nichola C.; Abian, Olga (Biochimica et biophysica acta. General subjects, 2018)
Differential Scanning Calorimetry (DSC) is a technique traditionally used to study thermally induced macromolecular transitions, and it has recently been proposed as a novel approach for diagnosis and monitoring of several diseases. We report a pilot study applying Thermal Liquid Biopsy (TLB, DSC thermograms of plasma samples) as a new clinical approach for diagnostic assessment of melanoma patients. Multiparametric analysis of DSC thermograms of patient plasma samples collected during treatment and surveillance (63 samples from 10 patients) were compared with clinical and diagnostic imaging assessment to determine the utility of thermograms for diagnostic assessment in melanoma. Nine of the ten patients were stage 2 or 3 melanoma subjects receiving adjuvant therapy after surgical resection of their melanomas. The other patient had unresectable stage 4 melanoma and was treated with immunotherapy. Two reference groups were used: (A) 36 healthy subjects and (B) 13 samples from 8 melanoma patients who had completed successful surgical management of their disease and were determined by continued clinical assessment to have no evidence of disease. Plasma thermogram analysis applied to melanoma patients generally agrees with clinical evaluation determined by physical assessment or diagnostic imaging (~80% agreement). No false negatives were obtained from DSC thermograms. Importantly, this methodology was able to detect changes in disease status before it was identified clinically. Thermal Liquid Biopsy could be used in combination with current clinical assessment for the earlier detection of melanoma recurrence and metastasis. TLB offers advantages over current diagnostic techniques (PET/CT imaging), limited in frequency by radiation burden and expense, in providing a minimally-invasive, low-risk, low-cost clinical test for more frequent personalized patient monitoring to assess recurrence and facilitate clinical decision-making. [Display omitted] •Thermal Liquid Biopsy is a blood test that can be easily and routinely performed.•This test can be applied routinely during the surveillance of melanoma patients.•Thermal Liquid Biopsy can be used to complement standard clinical assessment.•This methodology can provide a personalized diagnostic assessment of patient health.•Thermal Liquid Biopsy can aid physicians in the clinical decision-making process.